Contested ideas of regionalism in Asia - He, Baogang, 1957- (London And New York : Routledge, 2017)
'Deepening regionalism in Asia demands new leadership. Strong elites who are committed to a supranational identity are a minimum requirement of successful regionalism. Regional leaders are increasingly seen as a new set of leaders in Europe. Currently, Asian regional leaders largely come from the diplomacy community, or trade and economic sectors. Yet further regionalization demands a new type of leadership from civil society and citizens. In this context it is important to cultivate new regional leadership through the development of regional citizenship. This book examines contested ideas of regionalism in Asia with a particular focus on two competing ideas of pan-Asianism and Pacificism. It also identifies a new trend and contestation, the fundamental shift from a civilization understanding of regionalism to a technocratic and functional understanding of regionalism in the form of regulatory regionalism. It also examines the other contested imaginations of regionalism in Asia including elitist versus participatory approaches to regionalism, and democracy-centric versus nationalism-centric approaches to regionalism'--
Introduction to the idea of regionalism in Asia -- Pan-Asian ideas of regionalism -- Chinese ideas of regionalism -- Australian ideas of Asia-Pacific regionalism -- The competing norms of regionalism -- The contested ideas of regional governance -- The contested idea of security regionalism -- Toward hybrid regionalism? : pathways and pitfalls.
Includes bibliographical references : (pages 173-192) and index.
Keywords: Regionalism -- Asia; Regionalism (International organization) -- Asia; Asian cooperation; Asia -- Foreign relations -- 21st century